2021
DOI: 10.1111/1440-1681.13468
|View full text |Cite
|
Sign up to set email alerts
|

Clophosome alleviate dextran sulphate sodium‐induced colitis by regulating gut immune responses and maintaining intestinal integrity in mice

Abstract: Inflammatory bowel disease (IBD) is a chronic progressive disorder characterized by complicated gastrointestinal inflammation. Research on therapeutic agents is still urgent due to the lack of satisfactory treatments. Gut macrophages are considered to be predominant in excessive inflammatory responses. Thus, we aimed to investigate whether depletion of macrophages would have a beneficial effect on IBD and could be a potential therapeutic strategy. In this study, we established a 12‐day Dextran sodium sulphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Meanwhile, Au distribution in other organs and serum was similar between normal and IBD mice (Figure C–H). This phenomenon may due to the destruction of colonic epithelial integrity, as well as the increase in the number and activity of phagocytic immune cells during IBD. , Taken together, GA showed specific preference for colon distribution during IBD, supporting the possible role of GA against IBD.…”
Section: Resultsmentioning
confidence: 74%
“…Meanwhile, Au distribution in other organs and serum was similar between normal and IBD mice (Figure C–H). This phenomenon may due to the destruction of colonic epithelial integrity, as well as the increase in the number and activity of phagocytic immune cells during IBD. , Taken together, GA showed specific preference for colon distribution during IBD, supporting the possible role of GA against IBD.…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies have shown that IL-1β and IL-12 can promote the differentiation of helper T cells ( Mahida, 2000 ; Wang et al, 2021 ), and T helper 17 (Th17) cells are required for the development of IBD ( Geremia et al, 2014 ; Harbour et al, 2015 ; Alexander et al, 2022 ). IFN-γ–deficient Th17 cells maintained their Th17 phenotype but failed to induce colitis in mouse models, and IL-17A + IFN-γ + CD4 + T cells were considered to be more pathogenic ( Harbour et al, 2015 ; Tian et al, 2021 ). During DSS-induced colitis, IL-17A + IFN-γ + CD4 + T cell levels were significantly reduced after MNS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a zebrafish model of inflammation induced by tail amputation, beclomethasone decreases the number of macrophages that differentiate into M1 but does not affect the chemotactic migration of macrophages, strongly suggesting that the differentiation and migration of macrophages are independently regulated (Xie et al, 2019). Clophosome (clodronate disodium salt) depletes macrophages (Kobayashi et al, 2015); its application on macrophage‐related diseases such as trigeminal nerve pain (Batbold et al, 2017; Kanno et al, 2020), inflammatory bowel disease (Tian et al, 2021), and endometriosis (Sekiguchi et al, 2019) has been attempted. We have demonstrated that clophosome treatment inhibits activated SCs/GERCs with macrophage phenotypes, thereby enabling HC protection during viral infection, implying the possibility of using this compound to treat SSHL (Hayashi et al, 2021).…”
Section: Treatment For Sshl Targeting Activated Scs/gercs With the Na...mentioning
confidence: 99%